Faktor-Faktor Yang Mempengaruhi Pendapatan Industri Mikro dan Kecil (IMK) di Sumatera Barat - Gita Mutiara Warman; Ariusni Ariusni (Jurnal Kajian Ekonomi dan Pembangunan, 2023)
This study aims to determine; (1) To what extent does the number of workers affect the income of micro and small industries in West Sumatra, (2) To what extent do labor wages affect the income of micro and small industries in West Sumatra, (3) To what extent does technology affect the income of micro and small industries in Sumatra West, (4) To what extent working hours affect the income of micro and small industries in West Sumatra. This research is a descriptive and inductive type of research using panel data regression analysis using the Random Effect Model (REM) method with Cross Section 19 regencies/cities in West Sumatra and the 2018-2020 Time Series obtained from related institutions.The results showed that simultaneously, the variable number of workers, labor wages, technology, and working hours had a positive and significant influence on the Income of Micro and Small Industries (IMK) in West Sumatra. Furthermore, partially (1) the number of workers has a positive and significant effect on the income of micro and small industries (IMK) in West Sumatra, (2) the wages of labor have a positive and significant effect on the income of micro and small industries (IMK) in West Sumatra, ( 3) Technology has a negative and significant effect on Micro and Small Industry (IMK) Income in West Sumatra, (4) Working Hours has a positive and insignificant effect on Micro and Small Industry (IMK) Income in West Sumatra. So it can be concluded that the level of education, labor wages, technology, number of workers, and working hours are important aspects of the income of micro and small industries in West Sumatra.